Konstitusionalitas Kebijakan Belanja Subsidi Bahan Bakar Minyak dalam Anggaran Pendapatan dan Belanja Negara - Abidin, M. Zainul (Mahkamah Konstitusi Republik Indonesia, 2013)
The aims of this research was first, examining the harmony of the policy of fuel subsidy in the State Budget Law based on the 1945 Constitution of the Republic of Indonesia and second, observing the subsidy policy can be taken under Article 33 and 34 of the Constitution. This research used the literature studies. Data obtained from literature studies were discriptively and qualitativly analyzed used by the laws and public finance theories. It was concluded that the allocation policy of fuel subsidy in the budget in accordance with Article 23 paragraph (1) and Article 33 paragraph (3), ie in order to achieve maximum prosperity for the people. In the current situation, the policy of subsidized fuel does not accord the principle of efficiency with justice, continuity, and environmental perspective (Article 33, paragraph 4). Pursuant to Article 34 paragraph (1) and (2) Constitution, the subsidy policy should be focused to meet the needs of the poor / impoverished persons, inadequate and underprivileged.